A proportion of primary squamous cell carcinomas of the parotid gland harbour high‐risk human papillomavirus. Issue 6 (23rd August 2016) - Xu, Bin; Wang, Lu; Borsu, Laetitia; Ghossein, Ronald; Katabi, Nora; Ganly, Ian; Dogan, Snjezana
Abstract : Aims: In the current study, we aimed to examine primary parotid squamous cell carcinoma (ParSCC) for the presence of high‐risk human papillomavirus (HR‐HPV) and associated molecular alterations. Methods and results: Eight cases of ParSCC were retrieved after a detailed clinicopathological review to exclude the possibility of metastasis and/or extension from another primary site. HR‐HPV status was determined on the basis of immunohistochemistry (IHC) for p16 expression and chromogenic in‐situ hybridization (CISH) for HR‐HPV. All cases were genotyped with a multiplexed mass spectrometry assay interrogating 91 hotspot mutations in eight cancer‐related genes ( EGFR, KRAS, NRAS, BRAF, PIK3CA, AKT1, MEK1 and ERBB2 ), and studied by fluorescence in‐situ hybridization for PTEN copy number alteration. Three of eight cases (37.5%) were positive for the presence of HR‐HPV by CISH and p16 IHC. One of three (33%) HR‐HPV‐positive cases harboured a PTEN hemizygous deletion, and one (33%) HR‐HPV‐positive case harboured a PIK3CA E545K somatic mutation. No alteration of the PTEN–PI3K pathway was detected in HR‐HPV‐negative tumours. Over a median follow‐up period of 66.2 months, only the patient with the HR‐HPV‐positive PIK3CA ‐mutated tumour died of his disease, the remaining seven patients being disease‐free. Conclusions: Given the established aetiological role of HR‐HPV in other head and neck squamous cell carcinomas, it is likely that HR‐HPV represents an oncogenic driver in the pathogenesis of more than one‐third of ParSCCs. The presence of HR‐HPV in ParSCC may be coupled with alterations in the PTEN–PI3K pathway. Further studies on HR‐HPV and the molecular characterization of a larger number of ParSCCs are needed to determine the clinical significance of these findings.